Seudónimo
Seudónimo
12-06-2016
Mathematics
contestada
When x = −1, 3x + 9 equals
Respuesta :
JennW1
JennW1
12-06-2016
3(-1) + 9= -3 + 9= 6 that's the answer
Answer Link
hezekiah
hezekiah
12-06-2016
Plug in the x values.
3(-1)+9=?
3(-1)= -3
-3+9= 6
The answer is 6.
Answer Link
VER TODAS LAS RESPUESTAS ( 28+ )
Otras preguntas
Why can you remove paint with white spirit but not water?
How do you say Paris is a beautiful place, the attractions are really beautiful In French
factor using ac-method and factor completely, 25x²-30x--40 (help)
factor using ac-method and factor completely, 25x²-95x-20= ______ thanx for the help.
factor the trinomial, 14c³-33c²+18c= ______ (factor completely)
factor the trinomial, 14c³-33c²+18c= ______ (factor completely)
Which of the following mathematical expressions is equivalent to the verbal expression “A number, x, squared is 39 more than the product of 10 and x” ? F. 2x =
How do you say Paris is a beautiful place, the attractions are really beautiful In French
why a ladder would be useful if you had to rescue someone from an icy pond
factor the trinomial, 14c³-33c²+18c= ______ (factor completely)